Midwifery educators' knowledge of antenatal exercises in selected Nigerian midwifery schools - Mary M. Ojong-Alasia; Seepaneng S. Moloko-Phiri; Molekodi J. Matsipane; Ushotanefe Useh (AOSIS, 2024)
Background: Exercise during pregnancy is beneficial to both the pregnant woman and the foetus. Midwifery educators play a crucial role in ensuring that midwifery students receive the knowledge and training needed to demonstrate antenatal exercises. To ensure that their students understand and deliver adequate antenatal care, midwifery educators should be highly knowledgeable in pregnancy-related exercises. Objectives: The study was conducted to determine the knowledge of midwifery educators about antenatal exercise. Method: A descriptive cross-sectional study was conducted of the knowledge about antenatal exercises by midwifery educators. A purposive total population of 54 midwifery educators from three midwifery schools in Cross River State, Nigeria, was included in the study. Questionnaires were used for data collection, and Statistical Package for Social Sciences (SPSS) version 27 was used for data analysis. Ethical issues and rigour were maintained. Results: The study revealed that antenatal exercises are included in the midwifery curriculum and exercise demonstration were mainly done by midwifery educators and clinical instructors. The majority (n = 34, 66.7%) of the respondents were knowledgeable about World Health Organization (WHO) guidelines for exercise during pregnancy and had an average knowledge of the ideal antenatal exercises. Conclusion: Midwifery educators have average knowledge of the ideal antenatal exercises, which prompts the development of an exercise programme to guide midwifery training and practice. Midwifery educators should collaborate with exercise specialists to teach and demonstrate antenatal exercises. Contribution: The study highlighted the need for midwifery educators to obtain more information on antenatal exercises to adequately prepare midwifery students for evidence-based exercise care for pregnant women.